2008
DOI: 10.1002/tox.20460
|View full text |Cite
|
Sign up to set email alerts
|

Ultimobranchial gland of a freshwater teleost, Heteropneustes fossilis, in response to cadmium treatment

Abstract: Heteropneustes fossilis were subjected to 288 mg/L (0.8 of 96 h LC(50)) and 72 mg/L (0.2 of 96 h LC(50)) of cadmium chloride for short-term and long-term experiments, respectively. After sacrificing the fish, the blood was collected on 24, 48, 72, and 96 h in short-term and after 7, 14, 21, and 28 days in long-term experiment and analyzed for plasma calcium levels. Also, ultimobranchial glands were fixed on these intervals. The plasma calcium levels of short-term cadmium-exposed fish remain unchanged after 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
8
10
0
Order By: Relevance
“…Effects of botanical pesticides (except synthetic pyrethroids) have not been reported earlier on the blood calcium content of fish; hence, this study is the first report. This is in conformity with the reports of earlier investigators who have also noticed decreased blood calcium content after exposing the fish to various toxicantscypermethrin (Mishra et al 2001;Mishra et al 2010a, b;Pandey et al 2009), aldrin (Singh et al 1996), malachite green (Srivastava et al 1995), cadmium (Pratap et al 1989;Rai et al 2009), propoxur (Singh et al 1997), formithion (Singh et al 1997), lead (Rai et al 2010), and deltamethrin (Srivastav et al 1997;. However, no effect has been observed in blood calcium content of DDT-treated flounders Platichthys flesus (Haux 1979), methoxychlor-treated northern puffer Sphaeroides maculatus (Eisler 1967), cadmium-exposed Oncorhynchus niloticus (Oner et al 2008) and bifenthrin-treated rainbow trout Oncorhynchus mykiss (Velisek et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Effects of botanical pesticides (except synthetic pyrethroids) have not been reported earlier on the blood calcium content of fish; hence, this study is the first report. This is in conformity with the reports of earlier investigators who have also noticed decreased blood calcium content after exposing the fish to various toxicantscypermethrin (Mishra et al 2001;Mishra et al 2010a, b;Pandey et al 2009), aldrin (Singh et al 1996), malachite green (Srivastava et al 1995), cadmium (Pratap et al 1989;Rai et al 2009), propoxur (Singh et al 1997), formithion (Singh et al 1997), lead (Rai et al 2010), and deltamethrin (Srivastav et al 1997;. However, no effect has been observed in blood calcium content of DDT-treated flounders Platichthys flesus (Haux 1979), methoxychlor-treated northern puffer Sphaeroides maculatus (Eisler 1967), cadmium-exposed Oncorhynchus niloticus (Oner et al 2008) and bifenthrin-treated rainbow trout Oncorhynchus mykiss (Velisek et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…In vertebrates, calcium plays a vital role in a variety of biological processes. Although there exist several reports regarding the impact of toxicants on electrolyte composition of the blood (Suzuki et al 2006;Rai et al 2009;Velisek et al 2009;Srivastav et al 2010;Mishra et al 2010a, b), there exist no information regarding the impact of green pesticides on blood electrolytes of fish. Hence, it was aimed in the present investigation to study the toxic effect of a green pesticide Nerium indicum leaf extract on the freshwater teleost Heteropneustes fossilis in terms of serum calcium and phosphate levels.…”
Section: Introductionmentioning
confidence: 97%
“…To the best of our knowledge, the effect of botanical pesticides (except synthetic pyrethroids) on the blood calcium content of fish has not been reported earlier, hence this study provides the first report on this aspect. This observation regarding the decrease of blood calcium content after E. tirucalli latex exposure to fish derive support from the earlier investigators who have also reported hypocalcemia in the fish treated with various toxicants -cypermethrin (Pandey, Malviya, and Das 2009;Mishra et al 2010aMishra et al , 2010b, deltamethrin , aldrin (Singh, Das, and Singh 1996), cadmium (Pratap et al 1989;Rai et al 2009), propoxur and formothion (Singh, Das, and Srivastava 1997). On the other hand, elevated calcium levels of fish have been noticed after exposure to pesticides (Dalela et al 1981;Sharma et al 1982;Suzuki et al 2006).…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, phosphorus is required for intermediary metabolism (phosphorylated intermediates), genetic information (DNA and RNA), phospholipids, enzyme/protein components (phosphohistidine, phosphoserine), and membrane structure (Norman and Litwack 1987). Although there exists several reports regarding the impact of several pollutants on electrolyte composition of the fish blood (Suzuki et al 2006;Rai et al 2009;Velisek, Svobodova, and Piackova 2009;Mishra et al 2010aMishra et al , 2010bSrivastav et al 2010) but there exist no information regarding the impact of botanical pesticides on blood electrolytes of fish. Therefore, this study was aimed to investigate the effects of a botanical pesticide, E. tirucalli latex on blood electrolytes of a freshwater catfish Heteropneustes fossilis.…”
Section: Introductionmentioning
confidence: 97%
“…There existed no report regarding the effects of azadirachtin on the activity of fish UBG. In past, few investigators had noticed hypocalcemia and inactivity of UBG in fish after exposure to different toxicants -deltamethrin , metacid (Mishra, Srivastav, and Srivastav 2004), cypermethrin (Mishra, Srivastav, and Srivastav 2005), and cadmium (Rai et al 2009). The present study also derives support from the earlier reports in which hypoactivity/inactivity of the UBG had …”
Section: Discussionmentioning
confidence: 97%